PCB Design Guide to Via and Trace Currents and Temperatures - Brooks, Douglas (Artech House, 2021)
A very important part of printed circuit board (PCB) design involves sizing traces and vias to carry the required current. This exciting new book will explore how hot traces and vias should be and what board, circuit, design, and environmental parameters are the most important. PCB materials (copper and dielectrics) and the role they play in the heating and cooling of traces are covered. The IPC curves found in IPC 2152, the equations that fit those curves and computer simulations that fit those curves and equations are detailed.Sensitivity analyses that show what happens when environments are varied, including adjacent traces and planes, changing trace lengths, and thermal gradients are presented. Via temperatures and what determines them are explored, along with fusing issues and what happens when traces are overloaded. Voltage drops across traces and vias, the thermal effects going around right-angle corners, and frequency effects are covered. Readers learn how to measure the thermal conductivity of dielectrics and how to measure the resistivity of copper traces and why many prior attempts to do so have been doomed to failure. Industrial CT Scanning, and whether or not they might replace microsections for measuring trace parameters are also considered.